A 2020 Update on 20/20 X 2: Diplopia after Ocular Surgery: Diplopia after Orbital Surgery. Issue 4 (2nd October 2021) - Archer, Steven M.
ABSTRACT: In a review of 261 strabismus surgeries performed after previous orbital surgery, it was found that diplopia associated with orbital surgery most commonly occurs after orbital decompression for thyroid eye disease or after repair of orbital fractures. Other types of orbital surgery account for only a small number of cases. While the orbital surgery itself may contribute to the development or worsening of diplopia, in most cases, the post-operative strabismus is largely attributable to the underlying disease or trauma. However, in a small number of cases, a specific surgical misadventure can result in diplopia.